Complete mitochondrial genome of Glomeridesmus spelaeus (Diplopoda, Glomeridesmida), a troglobitic species from iron-ore caves in Eastern Amazon. Issue 3 (2nd July 2020) - Nunes, Gisele Lopes; Oliveira, Renato Renison Moreira; Pires, Eder Soares; Pietrobon, Thadeu; Prous, Xavier; Oliveira, Guilherme; Vasconcelos, Santelmo
Abstract: We report the complete mitochondrial genome sequence of Glomeridesmus spelaeus, the first sequenced genome of the order Gomeridesmida. The genome is 14, 825 pb in length and encodes 37 mitochondrial (13 PCGs, 2 rRNA genes, 22 tRNA) genes and contains a typical AT-rich region. The base composition of the mitogenome was A (40.1%), T (36.4%), C (15.8%), and G (7.6%), with an GC content of 23.5%. Our results indicated that G. spelaeus is only distantly related to the other Diplopoda species with available mitochondrial genomes in the public databases. As the broadest genetic characterization of a Glomeridesmida species available to date, the mitogenome of G. spelaeus will help understanding the evolution of such a little-known millipede group. Also, our data will be important for the characterization and conservation of the diverse invertebrate troglofauna of the Amazonian caves.